A staggered type of 0D/2D CuInS2/NiAl-LDH heterojunction with enhanced photocatalytic performance for the degradation of 2,4-Dichlorophenol - Wang, Tao; Men, Qiuyue; Liu, Xiqing; Zhan, Hongquan; Wang, Yongqing (Separation and purification technology, 2022)
•0D CuInS2 enhanced the photocatalytic performance of 2D NiAl-LDH.•Large BET surface and efficient separation of photo-induced electron-hole pairs.•A band matching within the n-n junction for efficient internal charge transfer. 0D/2D interface heterostructure of 0D CuInS2 and 2D NiAl-LDH were obtained via strong interfacial contact. Mott-Schottky analysis confirmed both materials were n-type feature. Thus, a staggered n-n heterojunction was formed via the balance of Fermi level. This 0D/2D composite exhibited enchantable activity for photocatalytic degradation 2,4-Dichlorophenol under visible-light illumination, far superior than pure CuInS2 and NiAl-LDH. The improvement of photocatalytic performance mainly attributed to the large BET surface area and interfacial contact, which resulted in more active sites, effective charge separation and transfer. Moreover, the optimal CuInS2/NiAl-LDH composite showed higher photostability for cycle experiments. At the same, the possible photocatalytic reaction process was proposed based on the trapping experiments, ESR technique and band position. This work provided a theory and foundation for designing and preparing of 0D/2D heterostructure system for photocatalytic application.